A Critical Review on Tamaka Shwasa (Bronchial Asthma) - Kaswan, Sushil Kumar; Gupta, Nisha; Chaudhary, Kiran (International Research Journal of Ayurveda & Yoga, 2022)
Tamaka Shwasa is a broad term, which includes many diseases where dyspnoea is a characteristic symptom. There are five classes of shwasa: Kshudra, Tamak, Chhinna, Maha and Urdhava shwasa. Tamak shwasa is Kaphaand Vatadominant. Tamak shwasa is main disease of pranvaha strotas. It is of two types- Santamak and Pratamaka shwasa. Acharya Charaka described that Tamaka Shwasa is Yappya type of disease. The etiological factors of Tamaka Shwasa are mentioned with variable multiplicity of diet, lifestyle and consequences of diseases. Every ayurveda physician should have the great knowledge of Tamaka Shwasa to decide different aspect of treatment.